أثر الأنماط القيادية على أداء العاملين - دراسة حالة بمصنع عموري لصنع الأجر - Yousfi, Ahmed amine; Naidjat, Abdelhamid (Finance and Business Economies Review, 2018)
This study aimed to determine the effects of leadership styles (Transformational Leadership, Transactional Leadership and Laissez faire Leadership) on the performance of employers in the factory of Amouri that produces bricks in the state of Laghouat. And to achieve the study objectives the study model was developed based on previous studies in this field, the questionnaire was distributed to a sample consists (142). statistical package for social science (SPSS) were used to analyse the collected data, as the results showed that there is no significant effect of laisser-faire leadership and transformational leadership on the employers performance, also there is significant effect of the transactional leadership on the employer’s performance. The study recommended the need to give more attention and clarify the leading role of leadership in the factory, by providing the factory employers with theoretical knowledge that highlights the importance of leadership and its styles to achieve the objectives of the factory, attention to factors and characteristics that lead to high level of performance of workers.